THE INFLUENCE OF OWNERSHIP STRUCTURE ON EARNINGS MANAGEMENT - Alzura, Mishel Vierman; Rudyanto, Astrid (E-Jurnal Akuntansi TSM, 2025)
The purpose of this research is to obtain empirical evidence on the factors influencing earnings management, specifically, the influence of managerial ownership, institutional ownership, family ownership, firm size, leverage, profitability, audit quality, sales growth, and board size on earnings management. The population used in this study consists of all consumer non-cyclical and cyclical companies listed on the Indonesia Stock Exchange from 2020 to 2022, and purposive sampling is used as the sampling method. With this method, it was found that sixty-six (66) consumer non-cyclical and cyclical companies met the sampling criteria and were selected as the sample, providing a total of 198 data points. This research utilizes multiple regression analysis to analyze the data. The results obtained from multiple regression show that audit quality and the board size have an impact on earnings management. Conversely, other independent variables, namely managerial ownership, institutional ownership, family ownership, company size, leverage, and profitability, do not affect earnings management.